Economic Importance of the Belgian Ports: Report 2005. Flemish maritime ports and Liège port complex - Frédéric Lagneaux (National Bank of Belgium, 2007)
This paper is an annual publication issued by the Microeconomic Analysis service of the National Bank of Belgium. The Flemish maritime ports - Antwerp, Ghent, Ostend, Zeebrugge - and the Autonomous Port of Liège play a major role in their respective regional economies and in the Belgian economy, not only in terms of industrial activity but also as intermodal centres facilitating the commodity flow. This update paper provides an extensive overview of the economic importance and development of the Flemish maritime ports and the Liège port complex in the period 2000 - 2005, with an emphasis on 2005. Focusing on the three major variables of value added, employment and investment, the report also provides some information about the financial situation in each port. A global indication concerning the financial health of the companies studied is also provided. These observations are linked to a more general context, along with a few cargo statistics. Annual accounts data from the Central Balance Sheet Office were used for the calculation of direct effects, the study of financial ratios and the analysis of the social balance sheet. The indirect effects of the activities concerned were estimated in terms of value added and employment, on the basis of data from the National Accounts Institute. 2005 was a year of steady growth for most Flemish maritime ports, in terms of quantity of cargo handled and value added, although there was a slight deceleration in comparison to the previous year. The employment situation was, by contrast, somewhat mixed, while investment soared, far exceeding the pace recorded since 2000. The current changes in world trade patterns are having a substantial impact on the operations of the Flemish and Liège ports, situated at the heart of one of the wealthiest and busiest trading regions of the world. To cope with the accelerating internationalisation of port competition and the tremendous growth of containerised seaborne transport, the ports concerned need to constantly adapt their infrastructures, through innovation and investment. As major logistic centres, they have to face the challenge of responding to increasing demand in terms of capacity, while adding as much value as possible to the goods passing through them. Accessibility and seamless connections with the hinterland are key to their success and durability. This has become absolutely vital in a climate of growing regional and international competition, accentuated by the booming Asian economies. The port of Liège is striving to turn a threat into an opportunity. In the wake of the Cockerill Sambre blast furnace closure, the Liège port complex is undergoing a major restructuring. Cargo figures were down sharply in 2005, while the economic situation of the area was dominated by stagnation or decline in terms of value added, employment and investment. However, this fall could be shortlived since the revival expected from the development of value-added logistics will also generate increased activity, traffic and demand for manpower. The present report provides a comprehensive account of these issues, giving details per economic sector, though the comments are confined to the main changes that occurred in 2005.
Keywords: C67; H57; J21; L22; L91; L92; R15; R34; R41; 330; branch survey; maritime cluster; subcontracting; indirect effects; transport intermodality; public investments.